REBECA trial: a new piece of the evidence for bevacizumab in platinum-resistant recurrent ovarian cancer - Lavacchi, Daniele; Fancelli, Sara; Gatta Michelet, Marta Rita; Catalano, Martina; Roviello, Giandomenico (Translational Cancer Research; Vol 9, No 2 (February 28, 2020): Translational Cancer Research, 2020)
Lee et al. (1) evaluated the efficacy and safety of bevacizumab in combination with single-agent chemotherapy for platinum-resistant ovarian cancer in a large retrospective analysis involving Korean women with platinum-resistant recurrent ovarian cancer from 27 different institutions.